2020
DOI: 10.1016/j.conbuildmat.2019.117277
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of GFRP bond behaviour for the design of sustainable reinforced seawater concrete structures

Abstract: Freshwater is an increasingly scarce resource. Its use in the production of concrete is one important contributor to its fast depletion. Alternatively, the use of seawater for reinforced concrete production, combined with the use of glass fibre reinforced polymers (GFRP) as reinforcement, may represent an interesting solution to increase concrete sustainability. The objective of this paper is to explore this promising solution through the development of concrete compositions with seawater. Additionally, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…Whilst, magnesium hydroxide (Mg(OH) 2 ) and gypsum (CaSO 4 ·2H 2 O) also bring expansion crystallization pressure to concrete and lead strength loss (Al-Amoudi 2002). Additionally, Sergio et al (2020) assessed the GFRP bond behavior in reinforced seawater concrete and showed that the maximum pullout force and shear strength were slightly lower when tap water was replaced by seawater to mix PC concrete. Therefore, it could be concluded that using seawater as mixing water in PC-based concrete could decrease the bond strength of GFRP.…”
Section: Resultsmentioning
confidence: 99%
“…Whilst, magnesium hydroxide (Mg(OH) 2 ) and gypsum (CaSO 4 ·2H 2 O) also bring expansion crystallization pressure to concrete and lead strength loss (Al-Amoudi 2002). Additionally, Sergio et al (2020) assessed the GFRP bond behavior in reinforced seawater concrete and showed that the maximum pullout force and shear strength were slightly lower when tap water was replaced by seawater to mix PC concrete. Therefore, it could be concluded that using seawater as mixing water in PC-based concrete could decrease the bond strength of GFRP.…”
Section: Resultsmentioning
confidence: 99%
“…A lower water-cement ratio was also used in seawater concrete because the salinity of the seawater was found to affect the overall performance of the concrete (Dhondy et al, 2021). In addition, the use of seawater would slightly reduce the slump and spread of cement paste generated in the concrete mixture compared to Da B et al, 2021;Li et al, 2021;Yue C et al, 2021;Dhondy et al, 2020;He X et al,2020;Yin et al, 2020;Parvizi et al, 2020;Chen G et al, 2020;Mansyur & Permana, 2020;Ma H et al, 2020;Gao et al, 2020;Soares et al, 2020;Adnan et al, 2020;Li, L. G., et al, 2019;;Montanari L. et al, 2019;Yu H et al, 2019;Gong W et al, 2019;Madona & Sivakumar, 2019;Jiang et al, 2019;Younis et al, 2019;Tan Y et al, 2018;Younis et al, 2018;Duan et al, 2015) Flexural strength 5 Gao et al, 2020;Parvizi et al, 2020;Jiang et al, 2019;Duan et al, 2015) Splitting tensile strength 4 (Ting M.Z.Y. et al, 2020;Parvizi et al, 2020;Yin et al, 2020;Younis et al, 2018) that of freshwater (Younis et al, 2018).…”
Section: Effect Of Seawater On Concrete Workability and Densitymentioning
confidence: 99%
“…13(Ting M. Z.Y. et al, 2021;Dhondy et al, 2021;Sun et al, 2021;Gao et al, 2020;Parvizi et al, 2020;Ting M. Z. Y et al, 2020;Chen G et al, 2020;Soares et al, 2020;Li, L. G., et al, 2019;Younis et al, 2018;Xiao et al, 2017;Duan et al, 2015) Fig.4 -…”
unclassified
“…Reinforced concrete (RC) has long been recognized as a construction material with excellent constructability, economic efficiency, fire resistance, and durability, but it naturally ages over time [1,2]. In addition, the performance and usability of the material slowly deteriorate due to changes in the surrounding environment [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%